2019
DOI: 10.1177/0725513619849651
|View full text |Cite|
|
Sign up to set email alerts
|

Boris Groys and the total art of Stalinism

Abstract: This paper’s core concern is Boris Groys’ theory of the total art of Stalinism, which is devoted to rewriting Soviet art history and reinterpreting Socialist Realism from the perspective of the equal rights between political and artistic Art Power. The aim of this article is to decode Groys and the total art of Stalinism, based on answering the following three questions: 1) why did Groys want to rewrite Soviet art history? 2) How did Groys re-narrate Soviet art history? 3) What are the pros and cons of his reo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Experiments showed that the combined damper have stable hysteretic behaviors. Liu et al [ 28 ] also investigated a type of hybrid damper for RCBs, which include two steel plates and a VED damper in horizontal parallel arrangement. Their viscoelastic material (VEM) is bonded to tooth profile steel plates to provide large in‐plane and out‐plane stiffnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that the combined damper have stable hysteretic behaviors. Liu et al [ 28 ] also investigated a type of hybrid damper for RCBs, which include two steel plates and a VED damper in horizontal parallel arrangement. Their viscoelastic material (VEM) is bonded to tooth profile steel plates to provide large in‐plane and out‐plane stiffnesses.…”
Section: Introductionmentioning
confidence: 99%